Novel Automated Suturing Technology for Minimally Invasive Mitral Chord Implantation: A Preclinical Evaluation Study. Issue 6 (November 2022) - Werner, Paul; Rath, Claus; Gross, Christoph; Ad, Niv; Gosev, Igor; Amirjamshidi, Hossein; Poschner, Thomas; Coti, Iuliana; Russo, Marco; Mach, Markus; Kocher, Alfred; Laufer, Guenther; et al.
Objective: This study evaluated the ergonomics and time requirements of using a novel automated suturing and titanium fastener deployment technology for chordal replacement in human heart specimens in open and minimally invasive cardiac surgery (MICS) simulators. Methods: Five cardiac surgeons used novel, manually powered expanded polytetrafluoroethylene (ePTFE) suturing devices to automate suture placement between mitral leaflets and papillary muscles in explanted cadaver hearts, along with customized titanium fastener delivery devices to secure suture and trim suture tails. This mitral chordal replacement test was conducted using surgical models simulating open and MICS mitral repair access. The study was approved by the institutional ethical board. Results: After a brief introduction to this technique using plastic models, study surgeons performed 48 chordal replacements in human mitral valves, placing 18 in an open model and 30 in a right minithoracotomy model. The time range to complete a single chordal replacement was between 55 s and 8 min, with an overall mean duration of 3.6 ± 1.5 min. No difference in duration of implantation was recorded for the MICS and open sternotomy simulators used. Good control of suture delivery was reported in 95.8% ( n = 46) of leaflet aspect of the sutures and in 100% ( N = 48) of papillary muscle sutures. Conclusions: Automated mitral chordal ePTFE suturing simulated through open and MICS access demonstrated quality handling and accurate placement of sutures in human heart specimens. A clinical trial using this technology is currently ongoing. This innovation may present an important advance facilitating enhanced minimally invasive mitral valve repair.